Distinct Pattern of Metastases in Patients with Invasive Lobular Carcinoma of the Breast - Mathew, Aju; Rajagopal, Padma S.; Villgran, Vipin; Sandhu, Gurprataap S.; Jankowitz, Rachel C.; Jacob, Mini; Rosenzweig, Margaret; Oesterreich, Steffi; Brufsky, Adam (Geburtshilfe und Frauenheilkunde, 2017)
Background Invasive lobular carcinoma (ILC) comprises around 10 – 15% of invasive breast cancers. Few prior studies have demonstrated a unique pattern of metastases between ILC and the more common invasive ductal carcinoma (IDC). To our knowledge, such data is limited to first sites of distant recurrence. We aimed to perform a comparison of the metastatic pattern of ILC and IDC at first distant recurrence as well as over the entire course of metastatic disease.Methods We used a prospectively collated database of patients with metastatic breast cancer. Breast cancer recurrence or metastases were classified into various sites and a descriptive analysis was performed.Results Among 761 patients, 88 (11.6%) were diagnosed with ILC and 673 (88.4%) with IDC. Patients with ILC showed more frequent metastases to the bone (56.8 vs. 37.7%, p = 0.001) and gastrointestinal (GI) tract (5.7 vs. 0.3%, p < 0.001) as first site of distant recurrence, and less to organs such as lung (5.7 vs. 24.2%, p < 0.001) and liver (4.6 vs. 11.4%, p = 0.049). Over the entire course of metastatic disease, more patients with ILC had ovarian (5.7 vs. 2.1%, p = 0.042) and GI tract metastases (8.0 vs. 0.6%, p < 0.001), also demonstrating reduced tendency to metastasize to the liver (20.5 vs. 49.0%, p < 0.001) and lung (23.9 vs. 51.9%, p < 0.001). All associations but bone held after sensitivity analysis on hormonal status. Although patients presenting with ILC were noted to have more advanced stage at presentation, recurrence-free survival in these patients was increased (4.8 years vs. 3.2 years, p = 0.017). However, overall survival was not (2.5 vs. 2.0 years, p = 0.75).Conclusion After accounting for hormone receptor status, patients with IDC had greater lung/pleura and liver involvement, while patients with ILC had a greater propensity to develop ovarian and GI metastases both at first site and overall. Clinicians can use this information to provide more directed screening for metastases; it also adds to the argument that these two variants of breast cancer should be managed as unique diseases.
Keywords: lobular carcinoma; breast cancer; late recurrence; survival; distant; metastasis